Efektifivas metode bradley terhadap intensitas nyeri persalinan di rumah sakit umum daerah Ir. Soekarno kabupaten brebes - Mardiani, Norma (Indonesia Berdaya, 2024)
Pain during childbirth occurs due to uterine contractions in the delivery phase of the fetus. The pain can manifest as local pain accompanied by cramps and a tearing sensation due to the distension and laceration of the cervix, vagina, or perineum tissues. Pain during the first stage of labor is primary pain resulting from cervical dilation and uterine contractions. This study aims to determine the Effectiveness of the Bradley Method on the Intensity of Labor Pain. In this research, the author will use the Quasi-Experiment method with a two-group pretest and posttest design, a non-equivalent control group consisting of two intervention groups. The sample for this study includes all mothers who will undergo normal delivery at the Ir. Soekarno Regional General Hospital in Brebes Regency in December 2023, totaling 31 individuals. Data collection will use observation sheets and Standard Operating Procedures (SOP). Data analysis will involve a paired-samples t-test. The research results indicate that the Bradley Method effectively reduces the Intensity of Labor Pain at Ir. Soekarno Regional General Hospital in Brebes Regency (r value = 0.000). Community health centers can play an active role in educating pregnant women about the benefits of the Bradley Method and supporting research by providing necessary facilities and information.